Efficacy and Safety of Apatinib Treatment for Advanced Cholangiocarcinoma After Failed Gemcitabine-Based Chemotherapy: An Open-Label Phase II Prospective Study - Zhang, Ge; Gong, Shuai; Pang, Lina; Hou, Lixia; He, Wei (Frontiers in Oncology, 2021)
Purpose: As a novel small-molecule vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor (VEGFR2-TKI), Methylsulfonic apatinib (apatinib) exhibits a specific antitumor effect in various solid tumors via inhibition of angiogenesis. The present study was performed to evaluate the clinical efficacy and safety of apatinib in the treatment of advanced cholangiocarcinoma after failed gemcitabine-based chemotherapy. Patients and methods: This was a prospective open-label phase II trial (NCT03521219). A total of 26 patients, in whom gemcitabine-based first-line chemotherapy for advanced intrahepatic cholangiocarcinoma had failed, were consecutively enrolled in a prospective, open, exploratory, and single-center clinical trial from November 2017 to November 2018. They were treated with apatinib mesylate second-line monotherapy (orally, 500 mg per day for a cycle of 28 days) until progressive disease or unacceptable toxicity. Using Response Evaluation Criteria in Solid Tumor version 1.1 (RECIST 1.1) and the Common Terminology Criteria for Adverse Events version 4.0 (NCI-CTCAE 4.0), the efficacy and adverse were evaluated, respectively. Kaplan-Meier method was used for survival analysis. Results: Follow-up ended on November 1, 2019. Six patients were lost to follow-up, 26 patients could be evaluated for progression-free survival (PFS) and short-term efficacy, and 24 patients were evaluated for median overall survival (OS). Among 26 patients, 1 patient (4%) showed complete response (CR), 4 patients (17%) showed partial response (PR), 10 patients (41.7%) stable disease (SD), and 9 patients (37.5%) had progressive disease (PD). Meanwhile, apatinib therapy achieved a disease control rate (DCR) of 62.5% and an objective response rate (ORR) of 20.8%. The median PFS was 95 days (95% confidence interval [CI]: 79.70–154.34 days), and the median OS was 250 days (95% CI: 112.86–387.14 days). Furthermore, univariate analysis revealed that age and tumor’s anatomic location significantly affected PFS (P<0.05). The most common clinically adverse events (AEs) included myelosuppression (69.2%), hypertension (57.7%), proteinuria (46.2%). The AEs were mild, mainly in grade 1 or 2, and no toxicity-induced death occurred. Conclusion: Apatinib monotherapy is an effective and promising regimen for treating patients with advanced cholangiocarcinoma who experienced failure of gemcitabine-based chemotherapy.